2003
DOI: 10.1242/jeb.00521
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and extracellular pH on metabolites: kinetics of anaerobic metabolism in resting muscle by 31P- and 1H-NMR spectroscopy

Abstract: Muscle metabolism is susceptible to a variety of stressing agents affecting particularly the overall rate of energy turnover. As is well known, temperature is a key environmental determinant of the activity of cellular multienzyme systems, such as muscle. In fact, this variable determines the kinetics and flux throughout biochemical pathways, particularly metabolic rates. Another key environmental determinant of cellular multienzyme system activity is intracellular pH. In general, owing to the presence of pH-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
(33 reference statements)
0
9
0
1
Order By: Relevance
“…A dual-tuned coil approach (such as (38,39)) could compare lactate results to phosphorus spectroscopy to further elucidate this relationship. This would investigate the interaction of lactate, pH, PCr, and other metabolites, as suggested previously by experiments with frog muscle (40). Performing these measurements on humans using clinical scanners will allow for the investigation of muscle energetics in exercise, peripheral vascular disease, muscle ischemia, and other phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…A dual-tuned coil approach (such as (38,39)) could compare lactate results to phosphorus spectroscopy to further elucidate this relationship. This would investigate the interaction of lactate, pH, PCr, and other metabolites, as suggested previously by experiments with frog muscle (40). Performing these measurements on humans using clinical scanners will allow for the investigation of muscle energetics in exercise, peripheral vascular disease, muscle ischemia, and other phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…A dual‐tuned coil approach (such as Boska et al (38) and Pipinos et al (39)) could compare lactate results to phosphorus spectroscopy to further elucidate this relationship. This would investigate the interaction of lactate, pH, phosphocreatine, and other metabolites, as suggested previously by experiments with frog muscle (40). Performing these measurements on humans, using clinical scanners, will allow for the investigation of muscle energetics in exercise, peripheral vascular disease, muscle ischemia, and other phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Hypometabolism in sartorius was reversible and repeatable (Feng, 1932), and the excess recovery heat after re-oxygenation was exquisitely responsive to the level of metabolic load imposed on the muscle during anoxia. Recent experiments have further demonstrated that (i) step changes in O 2 availability cause step changes in the stable metabolic heat production of isolated skeletal muscle Boutilier, 2001b) and of the whole animal (Schulz et al, 1991); (ii) the extent of suppression of muscle heat flux (to 20-30% of normal; Fig.·2) matches the reduction in muscle ATP synthesis as well as the anoxia-induced change in whole-animal metabolism (Schulz et al, 1991;West and Boutilier, 1998;Vezzoli et al, 2003;Vezzoli et al, 2004); and (iii) muscle ATP concentration is protected during anoxia. Anaerobic lactate accumulation is relatively low in anoxic sartorius and gastrocnemius (Vezzoli et al, 2004) at rest.…”
Section: Room Temperature Anoxic Responsesmentioning
confidence: 96%